Immune checkpoints and liver resection after neoadjuvant chemotherapy including bevacizumab in patients with microsatellite-stable colorectal liver metastases. Issue 1 (January 2022) - Stift, Judith; Graf, Alexandra; Neudert, Barbara; Herac, Merima; Woeran, Katharina; Tamandl, Dietmar; Laengle, Johannes; Schwarz, Christoph; Wrba, Friedrich; Kaczirek, Klaus; Stremitzer, Stefan
Abstract: Background: The clinical value of immune checkpoint expression as prognostic biomarker in bevacizumab-pretreated patients with resected microsatellite-stable (MMS) colorectal liver metastases is unclear and was retrospectively investigated in this study. Methods: Expression analyses of IDO-1, PD-L1, and CTLA-4 were performed by immunohistochemistry in resected bevacizumab-pretreated colorectal liver metastases. Association of immune checkpoint expression in tumor cells and immune cells with response and clinical outcome was investigated. Expression profiles were compared with those of patients with anti-EGFR-targeted therapy and lung metastases, respectively. Results: One hundred thirty-six patients with MMS disease were investigated (79 (58.1%) male/57 (41.9%) female, median age 62.9 years (range 31.0–80.4)). High expression of IDO-1 in immune cells was associated with longer OS (not reached versus 44.8 months, HR 0.23 (95% CI 0.09, 0.55), P  = 0.001). Low expression of CTLA-4 in tumor cells was associated with better histological response (26 major, 19 partial, 18 none versus 14 major, 23 partial, 30 none, P  = 0.032). Expression profiles differed compared to patients with anti-EGFR-targeted therapy and patients with lung metastases. Conclusion: Immune checkpoint expression was associated with response and survival. IDO-1 may serve as a novel prognostic and/or predictive biomarker in patients with MMS colorectal liver metastases.